2019
DOI: 10.1186/s12917-019-1785-0
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of bovine monocyte-derived macrophages with lipopolysaccharide, interferon-ɣ, Interleukin-4 or Interleukin-13 does not induce detectable changes in nitric oxide or arginase activity

Abstract: BackgroundBacterial lipopolysaccharide and interferon-γ stimulation of rodent macrophages in vitro induces up-regulation of inducible nitric oxide synthase, whereas interleukin-4 stimulation results in increased activity of arginase-1. Thus different stimulants result in differing macrophage phenotypes, appropriate for responses to a range of pathogens. The current study was conducted in order to determine whether bovine macrophages derived from monocytes and spleen respond similarly.ResultsLipopolysaccharide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
1
1
1
Order By: Relevance
“…Bovine macrophages are known to secrete significantly more NO in response to LPS than sheep and pigs, which are susceptible to Toxoplasma , LPS (Jungi et al, 1996 ; Young et al, 2018 ), suggesting that species-specific differences in susceptibility to Toxoplasma is due to differences in NO production. Although parasite growth was significantly restricted in stimulating bovine BMDMs with IFNγ-stimulated bovine BMDMs, IFNγ, on it's own, did not induce NO in bovine BMDMs, which is consistent with previous observations (Denis et al, 2005 ; Young et al, 2018 ; Imrie and Williams, 2019 ). In fact, intracellular parasite burden in IFNγ- and IFNγ+LPS-stimulated BMDMs were similar, despite the latter secreting significantly more NO.…”
Section: Discussionsupporting
confidence: 91%
“…Bovine macrophages are known to secrete significantly more NO in response to LPS than sheep and pigs, which are susceptible to Toxoplasma , LPS (Jungi et al, 1996 ; Young et al, 2018 ), suggesting that species-specific differences in susceptibility to Toxoplasma is due to differences in NO production. Although parasite growth was significantly restricted in stimulating bovine BMDMs with IFNγ-stimulated bovine BMDMs, IFNγ, on it's own, did not induce NO in bovine BMDMs, which is consistent with previous observations (Denis et al, 2005 ; Young et al, 2018 ; Imrie and Williams, 2019 ). In fact, intracellular parasite burden in IFNγ- and IFNγ+LPS-stimulated BMDMs were similar, despite the latter secreting significantly more NO.…”
Section: Discussionsupporting
confidence: 91%
“…A recent study reported that bovine MDMs stimulated with lipopolysaccharide (LPS) and IFN‐γ responded with increased transcription of the nos2 gene. However, these failed to translate into increased NO production 54 . Similarly, MDMs stimulated with PWM in the present study failed to produce NO.…”
Section: Discussioncontrasting
confidence: 59%
“…Multiple subsets of macrophages exist in the spleen 13 and some may have important roles bridging the innate and adaptive immunity 31 . The macrophage activation states have been mainly studied in bone marrow macrophages, but spleen macrophages are also able to reprogram between the M1 and M2 activation states in mice 32 , even if differences between macrophage activation exist in livestock species 33 . The dysregulated miRNAs are candidates for further research since they might play key roles in the immune response induced by aluminium adjuvants 34 .…”
Section: Discussionmentioning
confidence: 99%